2020
DOI: 10.1038/s41408-020-0322-5
|View full text |Cite
|
Sign up to set email alerts
|

Combining gene expression profiling and machine learning to diagnose B-cell non-Hodgkin lymphoma

Abstract: Non-Hodgkin B-cell lymphomas (B-NHLs) are a highly heterogeneous group of mature B-cell malignancies. Their classification thus requires skillful evaluation by expert hematopathologists, but the risk of error remains higher in these tumors than in many other areas of pathology. To facilitate diagnosis, we have thus developed a gene expression assay able to discriminate the seven most frequent B-cell NHL categories. This assay relies on the combination of ligation-dependent RT-PCR and next-generation sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Gene expression profiling (GEP) of 414 DLBCL patients treated with CHOP/R-CHOP were used as inputs for a SVM model which accurately stratified them in two biologically distinct subgroups [57]. Furthermore, a random forest algorithm was trained and validated to discriminate the most frequent B-cell NHL categories among 510 cases of NHL, based on ligation-dependent RT-PCR and next-generation sequencing (NGS) [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression profiling (GEP) of 414 DLBCL patients treated with CHOP/R-CHOP were used as inputs for a SVM model which accurately stratified them in two biologically distinct subgroups [57]. Furthermore, a random forest algorithm was trained and validated to discriminate the most frequent B-cell NHL categories among 510 cases of NHL, based on ligation-dependent RT-PCR and next-generation sequencing (NGS) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this, several works have reported the crescent use of AI and ML tools in the diagnosis of hematological diseases [14,15]. Among hematological malignancies, lymphoid neoplasms (LN) constitute one of the most active foci of research in this area, and different AI algorithms have been developed to improve accuracy in lymphoma subtyping [16,17], validation of prognostic models [18], and prediction of chemotherapy response [19,20]. However, a global analysis of the major trends, leading producers, and scientific mapping of AI and ML applications to diagnostic pathology in LN has not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrates the utility of using machine learning to capture information from gene expression analysis of B-cell lymphomas to aid in the subclassification by hematopathology. 27 Such assays are likely to become diagnostic companion tools and aid in the identification of targetable pathways. Potential hurdles for validating CNN use in a field with abundant subtypes is that large training sets have been shown to work best.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Previous studies have demonstrated that the classification of lymphoid neoplasms based on gene expression signatures was feasible and accurate [8][9][10][11] . To date, technologies have been developed to reliably quantify low-throughput gene expression in RNA from either fresh/frozen or formalin-fixed paraffinembedded (FFPE) tissue, allowing the development of clinically relevant RNA assays [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%